Avaliação de biomarcadores inovadores no diagnóstico precoce de lesão renal e endotelial em pacientes com anemia falciforme em uso ou não de hidroxiuréia - Laurentino, Marília Rocha (2020)
Sickle cell anemia (SCA) is an inherited disease characterized by homozygous hemoglobin S (HbSS). It is characterized by the long mortality rate due to chronic, endothelial damage and vaso-occlusion episodes, generating multiple damages. Changes in renal function are frequent in SCA, especially in adulthood. New renal function biomarkers are being studied in order to detect early renal changes in patients with SCA, such as kidney injury molecule 1 (KIM-1) and monocyte chemotactic protein (MCP-1). The aim of this study was to evaluate the renal biomarkers KIM-1 and MCP-1, associating them with biomarkers of hemolysis and endothelial damage. This is a cross-sectional, analytical and analytical study involving 92 SCA patients (62 using hydroxyurea and 25 non-use) of both sexes, attended at the hematology outpatient clinic of the Walter Cantídio University Hospital (HUWC) and Hemocenter (HEMOCE) in FortalezaCeará and 34 healthy cases as a control group. Biomarkers KIM-1, MCP-1, sindecano-1 and VCAM-1 were detected by immunoassay and as biomarkers of hemolysis and clinical data were collected from the medical records. The data were used using the statistical program GraphPad Prism. The level of significance was set at 5% (p <0.05). SCA patients without HU found an association of KIM-1 and MCP-1 with increased reticulocyte count. Syndecan-1 was associated with increased reticulocyte hemolysis, total bilirrubin (TB) and direct bilirubin (DB) biomarkers; and VCAM-1 an association with increased TB. Finally, without the use of HU, a presence of severe anemia and an increase in the cross-linking count influence KIM-1 and MCP-1 alterations, the risk groups for the increase of these biomarkers and the possible development of renal lesions. We can conclude that patients with SCA have a tendency to have kidney damage, they are associated with the presence of anemia and hemolysis, factors that include non-HU use, can interfere in the initiation and progress of sickle cell nephropathy.